2017
DOI: 10.1111/jspn.12191
|View full text |Cite
|
Sign up to set email alerts
|

Maternal concerns and perceptions of elementary school‐age children's weight status

Abstract: In order for school-based childhood obesity prevention and intervention programs to be successful, parents must accurately perceive their elementary school-age child's weight status. School nurses can be vital to these efforts through proper training and resources. Nurses can use the "School Nurse Childhood Obesity Toolkit" and motivational interviewing techniques to address parental concerns and perceptions prior to teaching behavior modification strategies to children/families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
3
2
Order By: Relevance
“…Mothers' weight status was a significant predictor of maternal perceptions of children's weight status only when children's weight status was not included in the model, which suggests that children's weight status is a more important determinant of mothers' perceptions of child weight than mothers' own weight status. As for concern, mothers' weight status was not associated with their concerns about child weight, which is in contrast to several studies reporting that parents with overweight or obesity were more likely to be concerned about child weight status than normal-weight parents (19)(20)(21)30,68) . It is important to note that most of these studies were conducted with White or Latino populations (19)(20)(21)30) or had a very small sample of Black/African-American parents (30,68) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Mothers' weight status was a significant predictor of maternal perceptions of children's weight status only when children's weight status was not included in the model, which suggests that children's weight status is a more important determinant of mothers' perceptions of child weight than mothers' own weight status. As for concern, mothers' weight status was not associated with their concerns about child weight, which is in contrast to several studies reporting that parents with overweight or obesity were more likely to be concerned about child weight status than normal-weight parents (19)(20)(21)30,68) . It is important to note that most of these studies were conducted with White or Latino populations (19)(20)(21)30) or had a very small sample of Black/African-American parents (30,68) .…”
Section: Discussioncontrasting
confidence: 99%
“…These feeding practices were previously determined not only to have a negative impact on children's diet quality but were also associated with excessive weight gain over time (9,10,15) . Although parents whose children have overweight or obesity are more likely to be concerned about their children's weight, children's age (16,17) and gender (13,18,19) , as well as parental weight status (19)(20)(21) , region of origin (22) and education level (23) also contribute to these concerns. In contrast, parental age, socio-economic status and marital status were found not to be associated with parental concerns about child weight (3,18,21) .…”
mentioning
confidence: 99%
“…Similarly, this systematic review aimed at identifying the differences between parental perception and the actual weight status of children worldwide, this finding reveals that majority of studies used verbal descriptions 51 . This review shows that parents' wrong perception regarding their children weight status was higher in parents compared to only mother (90%, 30% respectively) 23,24 , this finding is in accordance with previous findings of other study who reported a higher wrong perception in parents compared to only mother 52 , this can be explained by mothers having more concerned than fathers about their child's weight status. Noticeably, this systematic review revealed that obese children are often perceived as normal-weight children and not vice versa.…”
Section: Discussionsupporting
confidence: 92%
“…New research further shows that there is a fine line in how a parent processes information and behaves if they perceive a child is overweight, as this perception is not always followed by attempts to reduce the problem, but is clearly predictive of obesity in later life. Hernandez et al, 19 too recently found that even though mothers with higher body mass indices tended to be more concerned than those of normal weight about their child becoming overweight, concerned mothers had 82% lower odds of underestimating their child's weight. Other research by Hong et al, 35 shows that both parents and health professionals demonstrate low sensitivity in identifying children's weight status, so both may require a degree of appropriate education.…”
Section: Discussionmentioning
confidence: 99%
“…To assist in addressing all these overlapping issues, and to arrive at a more desirable outcome than is presently observed, careful needs assessments, followed by insightful culturally appropriate and targeted strategies, that include partnerships between parents, clinicians, dieticians, health educators, and school nurses are clearly indicated. However, according to Hernandez et al, 19 the key issue is that parents must be able to accurately perceive their child's weight status in the first place. In this regard, Hong et al, 37 suggest that family-based weight control interventions that incorporate education concerning the importance of overcoming parental misperceptions of the body weight may be helpful, while Hong et al, 22 suggest health professionals use the Centers for Disease Control and Prevention categories to facilitate parents' ability to accurately identify overweight or 'at risk' children.…”
Section: Discussionmentioning
confidence: 99%